Mitochondrial genome and plant taxonomy - Duminil, J. (Springer, 2014)
The lability in size, structure, and sequence content of mitochondrial genome (mtDNA) across plant species has sharply limited its use in taxonomic studies. However, due to the new opportunities offered by the availability of complete mtDNA sequence in plant species and the subsequent development of universal primers, the number of mtDNA-based molecular studies has recently increased. Historically, universal primers have enabled to characterize mtDNA polymorphism mainly by the RFLP technique. This methodology has been progressively replaced by Sanger DNA sequencing, which actually provides the full phylogenetic information content of a DNA fragment (single nucleotide, insertion/deletion, and single sequence repeat length polymorphism). This chapter presents a sequencing working protocol to be routinely used in mtDNA-based phylogenetic studies.